IMPLIKASI GURU PROFESIONAL DALAM PEMBENTUKAN KARAKTER SISWA - Wisnarni, Wisnarni (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2018)
Teachers as professional educators must have knowledge and abilities who suitable with their profession. The professionalism criteria educators have academic qualifications and competencies who includes; (1) Pedagogic Competence, (2) Personality Competence, (3) Professional Competence, and (4) Social Competence. All of these four competencies cannot stand alone, but are mutually integrated in learning; it means that they are based on one another components which underlie other components. Besides, to establish the children with character can be carried out by direct or indirect fostering of faith, worship, and character which is carried out gradually and continuously, as early as possible in accordance to the childrens’ habit and psychology development using various approaches. Meanwhile, among the right approaches is through a habitual approach, exemplary, educative and persuasive, advice and stories that can deep the heart. As exemplified by Allah and His Messenger in educating and teaching humans. The teacher professionalism will establish synergies between the implementation of knowledge transfer activities that continue to prioritize quality with the realization of moral students who uphold religious values. Building student character by instilling habits about good things so that students become understood (cognitive domain), instill values ​​and instill what is permissible and what is not (affective domain), able to do (psychomotor domain) and set an example of life ( living model)